The Existence of Islamic Student Organizations: How Student Organizations of Nahdlatul Ulama and Muhammadiyah Respond to the Challenges of the 21st Century - Nuruzzaman, Muhammad Adib; Ummah, Ilmi Izzatul; Faizah, Nur (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2025)
In the digital era, students face rapid changes in various fields, ranging from technological advancements to global culture, which often clash with Islamic values. This paper explains how the Nahdlatul Ulama Student Association (IPNU) and the Muhammadiyah Student Association (IPM)—the two largest Islamic student organizations in Indonesia—respond to the challenges of the 21st century. Using qualitative methods and a multiple case study design, the research collected data through interviews, document reviews, and literature studies. The data were then analyzed using a cross-case analysis method to compare the strategies employed by IPNU and IPM. The aim is to provide updated insights into the existence of Islamic student organizations in empowering youth amidst the dynamics of 21st-century modernization. The findings reveal that Nahdlatul Ulama, with its